Early Life and Oxidative Stress in Psychiatric Disorders: What Can we Learn From Animal Models? - Mhillaj, Emanuela; Grazia Morgese, Maria; Trabace, Luigia (Current Pharmaceutical Design, 2015)
Schizophrenia is a complex pathology characterized by the occurrence of a variety of symptoms classified as positive, negative and cognitive. Although the exact etiopathogenesis of this disorder has not been unraveled yet, many theories have been endorsed during the last years. Among these, the neurochemical theories have been the most suited, considering the dopaminergic and glutamatergic dysfunctions to be mainly responsible for psychotic symptoms. However, the lack of efficacy of the available drugs, namely antipsychotics, toward negative and cognitive symptoms led to hypothesize alternative approaches. In this regard, the neurodevelopmental theory of schizophrenia has emerged, proposing the association between the occurrence of environmental risk factors in early-life and the development of psychosis in late-life. In particular, exposure to early life stressing situations, such as pre- and peri-natal stress, has been suggested as a risk factor to d evelop psychopathologies in adulthood in people genetically predisposed. A crucial support in favor of this hypothesis came from neurodevelopmental animal models of schizophrenia, such as maternal malnutrition, maternal deprivation, maternal infections as well as post-weaning social isolation rearing. Moreover, data from these models, corroborated by clinical findings, indicate that oxidative and nitrosative stress play a crucial role in the etiopathogenesis of psychiatric disorders. In the present work, we reviewed the recent progress in literature regarding data available from animal models linking oxidative and nitrosative stress to psychiatric disorders in order to evaluate novel biomarkers of pathology as well as novel therapeutical targets.
Keywords: nitric oxide